2021
DOI: 10.3389/fmed.2021.737084
|View full text |Cite
|
Sign up to set email alerts
|

The Role of IL-37 and IL-38 in Obstetrics Abnormalities

Abstract: There are two fairly common complications during pregnancy, i.e., gestational diabetes mellitus (GDM) and pre-eclampsia, which are independent, but are also closely linked in prevalence in pregnant women, with potential serious adverse consequences. IL-37 and IL-38, which belong to the IL-1 superfamily, participate in anti-inflammatory responses. Dysregulation of IL-37 and IL-38 has been observed in many auto-immune diseases. IL-37 is substantially reduced in the umbilical cords and placentas of GDM subjects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…COVID-19 patients are characterized by increased expression of proinflammatory cytokines, such as IL-2, IL6, IL-17, and tumor necrosis factor-alpha (TNFα) [ 198 , 199 ]. During the development of pregnancy disorders, pro-inflammatory cytokines, such as IL-1β, IL-6, IL-17, and TNFα, are also significantly increased [ 200 , 201 ]. Moreover, there is an increased incidence of preterm birth and low birth weight in COVID-19-positive pregnant women [ 202 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 patients are characterized by increased expression of proinflammatory cytokines, such as IL-2, IL6, IL-17, and tumor necrosis factor-alpha (TNFα) [ 198 , 199 ]. During the development of pregnancy disorders, pro-inflammatory cytokines, such as IL-1β, IL-6, IL-17, and TNFα, are also significantly increased [ 200 , 201 ]. Moreover, there is an increased incidence of preterm birth and low birth weight in COVID-19-positive pregnant women [ 202 ].…”
Section: Discussionmentioning
confidence: 99%
“…As reviewed in this study, alterations in serum levels of IL-38 played a major role in the immunopathogenesis of many diseases, in which patients had been previously faced with a wide array of problems due to the lack of prognosis or accurate diagnosis and improper treatment [213][214][215][216][217][218][219][220][221]. At the time of the literature review for this systematic review study, as there is a global pandemic of Coronavirus, it has been demonstrated that anti-inflammatory properties of IL-38 can be considered as recently-emerged pharmacotherapies for alleviation of the inflammatory symptoms of patients with SARS-CoV-2 infection [186,222].…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…IL‐37, a member of the IL‐1 cytokine family identified in 2000, is an anti‐inflammatory cytokine known for its ability to reduce innate inflammation and suppress adaptive immune responses. Many types of immune and non‐immune cells produce IL‐37, including monocytes, macrophages, dendritic cells, B cells, plasma cells, natural killer cells and epithelial cells, in response to pro‐inflammatory stimuli 7 . Dysregulated production of IL‐37 has been associated with several human inflammatory conditions, such as enterocolitis, Behçet's disease, periodontitis, asthma, SARS‐CoV‐2 infection and liver inflammation 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Many types of immune and non‐immune cells produce IL‐37, including monocytes, macrophages, dendritic cells, B cells, plasma cells, natural killer cells and epithelial cells, in response to pro‐inflammatory stimuli. 7 Dysregulated production of IL‐37 has been associated with several human inflammatory conditions, such as enterocolitis, Behçet's disease, periodontitis, asthma, SARS‐CoV‐2 infection and liver inflammation. 8 Regarding T2DM, there is some evidence to suggest that IL‐37 may have a role in the pathogenesis.…”
Section: Introductionmentioning
confidence: 99%